Pengaruh Strategi Keungggulan Bersaing, Total Quality Management dan Keungggulan Bersaing terhadap Kinerja Perusahaan dengan moderasi Informasi Akuntansi Manajemen: Studi pada Perusahaan Manufaktur Industri Rokok di Kota Kudus - Agus Ahmad Mufad; Hexana Sri Lastanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The tobacco products industry (IHT) is one of the domestic strategic sectors that has high competitiveness and continues to make a significant contribution to the national economy. The contribution of this sector, which is categorized as local wisdom, includes employment, state revenue through excise and is an important commodity for farmers from plantation products in the form of tobacco and cloves. This study aims to determine the effect of Competitive Advantage Strategy, Total Quality Management and Competitive Advantage on Company Performance with moderation of Management Accounting Information. The population in this study were CEOs and/or Managers and Section/Branch Heads of 80 cigarette factories in Kudus Regency. Data was collected through distributing questionnaires online (Google Form) on WhatsApp media. The sample in this study was 127 respondents. Data processing and analysis using Structural Equation Modeling (SEM) analysis with Smart PLS 3 software. The results of this study indicate that competitive advantage strategy has no effect on company performance, total quality management has a positive effect on company performance, competitive advantage has no effect on company performance, management accounting information does not strengthen the effect of competitive advantage strategy on company performance, management accounting information strengthens the effect of total quality management on company performance, management accounting information strengthens the effect of competitive advantage on company performance.